AVALIAÇÃO DOS EFEITOS DE PLANTAS MEDICINAIS NO DESEMPENHO REPRODUTIVO E NO DESENVOLVIMENTO EMBRIOFETAL - Thais Arruda de Santana (2024)
Plants have been used for centuries as a natural resource for human survival, both as food and as a medicinal source. Dipteryx alata is a plant belonging to the Fabaceae family that is used in folk medicine as an anti-inflammatory, to aid weight loss, as an antivenom, healing agent, antioxidant and to reduce cholesterol. Guettarda viburnoides is used to treat inflammatory diseases. There are no studies in the literature that demonstrate prolonged effects of the use of these plants by pregnant women. In view of the above, the objective of this study was to evaluate the effects of these medicinal plants on reproductive performance and embryofetal development. For the study with D. alata sap, Swiss mice were randomly distributed into 4 experimental groups (n=10): Control group - the animals received the vehicle (distilled water) in the proportion of 0.1 mL/10 g of body weight (bw) by gavage (oral route - v.o.) from the 1st to the 18th day of gestation (d.g.); D. alata sap groups (SDa) – the animals received sap, instead of water, in dilutions of 25% (SDa25), 50% (SDa50) and 75% (SDa75). For the study with the ethanolic extract of G. viburnoides, the mice were randomly distributed into 3 groups (n = 10): Control group – the animals received saline solution in the proportion of 0.1 mL/10 g (bw; v.o.) from the 1st to the 18th d.g.; G. viburnoides ethanolic extract group (EEGv) – the animals were treated with EEGv at doses of 300 and 1000 mg/kg (c.p.; v.o.) from the 1st to the 18th d.g. The results demonstrated that SDa did not alter reproductive performance. However, it altered embryofetal development and the highest dose of SDa increased fetal weight, placental weight, placental index, and the frequency of external malformations and scoliosis (skeletal malformation). In addition, it reduced placental efficiency. The lowest dose increased the overall frequency of skeletal malformation. All doses reduced the frequency of visceral malformations. In view of the above, it is considered that SDa does not alter the reproductive performance of females, alters embryofetal development and has low teratogenic potential. The results of the study with EEGv demonstrated that there was no change in reproductive performance and embryofetal development. The individual and global evaluation of the frequency of external malformations showed no significant difference between the control group and the treated groups. In the evaluation of visceral malformation, it was observed that the highest dose of EEGv increased the frequency of mild hydrocephalus and the overall frequency of visceral malformations for the same group. The evaluation of skeletal malformations showed that there was no significant difference in the frequency of malformations in the individual analysis by alteration, however, in the global evaluation, an increase in the global frequency of skeletal malformations was observed in the group treated with the lowest dose of EGv. Therefore, it is considered that EEGv does not alter reproductive performance, does not alter embryofetal development and has low teratogenic potential.